THE AMIR WHO LEFT THE "HALF-KINGS" BEHIND OR AMIR ABDULAHAD - Abduvohidova Rukhshona Doniyorbek kizi (PEDAGOGS, 2025)
Abstract: This article provides information about the biography of one of the last Bukhara Mang’it emirs, Emir Abdulahadkhan, his accession to the Bukhara throne and the political and social situation of the emirate during his reign, his travels, and his relations with the Russian emperors.